THE CURRICULUM OF LOVE IN THE PERSPECTIVE OF THE QUR'AN AND ITS RELEVANCE TO ELEMENTARY EDUCATION IN MADRASAH IBTIDAIYAH - Nur Alfiyani; Moh. Ghoizi Eriyanto; Ivo Retna Wardani (Lembaga Penelitian dan Pengabdian Masyarakat STIES Babussalam, 2026)
This study aims to examine the concept of the Curriculum of Love in the perspective of the Qur'an and to analyze its relevance to elementary education in Madrasah Ibtidaiyah (MI). Using a library research approach with the content analysis method, this study examines Qur'anic verses containing values of love and compassion, namely rahmah, mawaddah, ihsan, and ukhuwwah, and contextualizes them with contemporary Islamic curriculum theories and elementary education. The findings indicate that the Qur'an provides a profoundly strong theological foundation for the concept of the Curriculum of Love, whose relevance to elementary education at MI can be analyzed through four main dimensions: developmental-psychological, juridical-normative, pedagogical-professional, and institutional-cultural. This study concludes that the Qur'an-based Curriculum of Love is not merely a normative concept, but an educational framework that has been scientifically proven effective and is juridically aligned with the goals of Indonesia's national education system.